2012
DOI: 10.1111/j.1463-1318.2011.02585.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum A toxin as a treatment for overactive rectum with associated faecal incontinence

Abstract: Patients with an 'overactive rectum' are a heterogeneous group, with varying causes of dysfunction. The dose of BT used was arbitrarily selected. Nevertheless, the study introduces a further therapeutic option in the treatment of FI caused by rectal overactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A single report of onabotulinumtoxinA (200-400 U) use in an Indiana pouch (neobladder from ascending colon and distal ileum) following cystectomy, resulting in incontinence control over 3 years is documented 19 Positive results have also been reported for rectal overactivity/fecal incontinence. 20 These studies and those in augmented bladders above remains unique in the context of intra-augment injections. The current market license for BOTOX is limited to injections in the detrusor muscle, and not into bowel.…”
Section: Discussionmentioning
confidence: 98%
“…A single report of onabotulinumtoxinA (200-400 U) use in an Indiana pouch (neobladder from ascending colon and distal ileum) following cystectomy, resulting in incontinence control over 3 years is documented 19 Positive results have also been reported for rectal overactivity/fecal incontinence. 20 These studies and those in augmented bladders above remains unique in the context of intra-augment injections. The current market license for BOTOX is limited to injections in the detrusor muscle, and not into bowel.…”
Section: Discussionmentioning
confidence: 98%
“…23 However, the risk of bowel impairment seems to be multifactorial and may include other confounding factors such as reduced rectal reservoir, diminished mobility at the level of the rectal scar, stenosis of rectal anastomosis, 24 and decrease in the ability to attenuate the transmission of high intracolonic pressure toward the anal sphincter. 25,26 The prevalence of postoperative constipation is high in patients managed by colorectal resection and report lesser satisfactory gastrointestinal scores when compared with those treated by rectal shaving. 27 However, in patients managed by rectal shaving or disc excision, preoperative constipation scores are not significantly improved by the surgery itself.…”
Section: Nerve Sparing In Endometriosis: Pessimism Of the Intellect Omentioning
confidence: 99%
“…Exclusion criteria were pregnancy, breastfeeding, psychiatric disorders, myasthenia gravis, polyradiculoneuropathy, history of inhalation pneumopathy, full-thickness rectal prolapse, extensive anal sphincter lesions, fecal impaction, and anorectal pathologies such as inflammatory bowel disease and cancer. The selected subjects were added to those from our previous study [6]. Patients provided written, informed consent for the endoscopic BTX-A injections.…”
Section: Patientsmentioning
confidence: 99%
“…Based on the experience of urologists treating overactive bladder, we hypothesized that BTX-A rectal/reservoir in-jections might inhibit spontaneous rectal/reservoir contractions and, at the same time, increase rectal/reservoir capacity and compliance, providing fecal incontinence relief for patients, with or without a hypercontractile rectum/reservoir. In a preliminary study, we demonstrated that the short-term results of six patients with severe fecal incontinence related to hypercontractile rectum or colonic pouch following proctectomy who received reservoir BTX-A injections were encouraging [6]. The aim of the present study was to assess the short-term clinical outcomes of a larger sample of patients with various etiologies underlying their fecal incontinence, whether or not they had rectal/reservoir contractile activity, following BTX-A injections.…”
mentioning
confidence: 90%